Multi-electrode array study of neuronal cultures expressing nicotinic β2-V287L subunits, linked to autosomal dominant nocturnal frontal lobe epilepsy. An in vitro model of spontaneous epilepsy - Gullo, Francesca; Manfredi, Irene; Lecchi, Marzia; Casari, Giorgio; Wanke, Enzo; Becchetti, Andrea (Frontiers in Neural Circuits, 2014)
Autosomal dominant nocturnal frontal lobe epilepsy (ADNFLE) is a partial sleep-related epilepsy which can be caused by mutant neuronal nicotinic acetylcholine receptors (nAChR). We applied multi-electrode array (MEA) recording methods to study the spontaneous firing activity of neocortical cultures obtained from mice expressing or not (WT) an ADNFLE-linked nAChR subunit (β2-V287L). More than 100,000 up-states were recorded during experiments sampling from several thousand neurons. Data were analyzed by using a fast sliding-window procedure which computes histograms of the up-state durations. Differently from the WT, cultures expressing β2-V287L displayed long (10-32 s) synaptic-induced up-state firing events. The occurrence of such long up-states was prevented by both negative (gabazine, penicillin G) and positive (benzodiazepines) modulators of GABAA receptors. Carbamazepine (CBZ), a drug of choice in ADNFLE patients, also inhibited the long up-states at micromolar concentrations. In cultures expressing β2-V287L, no significant effect was observed on the action potential waveform either in the absence or in the presence of pharmacological treatment. Our results show that some aspects of the spontaneous hyperexcitability displayed by a murine model of a human channelopathy can be reproduced in neuronal cultures. In particular, our cultures represent an in vitro chronic model of spontaneous epileptiform activity, i.e. not requiring pre-treatment with convulsants. This opens the way to the study in vitro of the role of β2-V287L on synaptic formation. Moreover, our neocortical cultures on MEA platforms allow to determine the effects of prolonged pharmacological treatment on spontaneous network hyperexcitability (which is impossible in the short-living brain slices). Methods such as the one we illustrate in the present paper should also considerably facilitate the preliminary screening of antiepileptic drugs, thereby reducing the number of in vivo experiments.